Does the Short Period of Resistance Training May Improve the Sleep Quality? Pilot Study - Polito, Luis Felipe Tubagi; Marin, Douglas Popp; Montenegro, Carla Giuliano Pinto de Sá; Zanetti, Marcelo Callegari; Junior, Marcelo Villas Boas; Dias, Helton Magalhães; Rica, Roberta Luksevicius; Mascarenhas, Júlia; Junior, Aylton Figueira; Brandão, Maria Regina Ferreira (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Purpose: The present study aimed evaluated the influence of exercise program on sleep quality of sedentary individuals. Methods: The study evaluated 30 subjects after resistance training session constituted by six multi-joints exercises (leg press, chest press, machine let pull down, seated machine shoulder press, crunches and machine trunk extension) three times a week for 40 days. The intensity of the effort was controlled using the follow criteria: the ideal repetitions for each set was between eight and fifteen. The Pittsburgh Sleep Quality Questionnaire (PSQI) was applied before and after training period. Results: There was a significant effect of short-term resistance training on all sub-scores of PSQI (p0.05). Conclusion: The resistance training program was able to improve the sleep quality in healthy subjects. In addition, the applicability of low-cost instruments (psychometric instruments like PSQI) to evaluate health parameters, which could be strengthened by other studies.